2022
DOI: 10.3390/children9020136
|View full text |Cite
|
Sign up to set email alerts
|

Early High-Dose Methylprednisolone Therapy Is Associated with Better Outcomes in Children with Acute Necrotizing Encephalopathy

Abstract: Background: The neurologic outcomes of acute necrotizing encephalopathy (ANE) are very poor, with a mortality rate of up to 40% and fewer than 10% of patients surviving without neurologic deficits. Steroid and immunoglobulin treatments have been the most commonly used options for ANE, but their therapeutic efficacy is still controversial. Method: We retrospectively reviewed the medical records of 26 children diagnosed with ANE. We also divided these patients into two groups: 21 patients with brainstem involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Hence, with these elements, we suggest that our patient's treatment blunted the immune response to the vaccine and explains the negative serologies. Rapid treatment may have influenced the positive outcome in our patient's situation, as has been retrospectively shown in children with ANE (25).…”
Section: Unfulfilledmentioning
confidence: 70%
“…Hence, with these elements, we suggest that our patient's treatment blunted the immune response to the vaccine and explains the negative serologies. Rapid treatment may have influenced the positive outcome in our patient's situation, as has been retrospectively shown in children with ANE (25).…”
Section: Unfulfilledmentioning
confidence: 70%
“…While ANE is certainly an uncommon sequela of COVID-19, the exact risk is difficult to estimate, in part because of underdiagnosis and underreporting. One recent literature review identified 23 published adult cases of COVID-19-related ANE, most of which occurred in patients without prior neurologic comorbidities [3]. Future populationbased studies would be instructive in determining the actual incidence of ANE in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Acute necrotizing encephalopathy (ANE) is a para-infectious autoimmune condition that typically affects children suffering from influenza, but has also been reported in adults and related to other viral infections [2,3]. ANE occurs within days to weeks of viral symptoms and fever and is often characterized by rapid progression to coma in the absence of cerebrospinal fluid (CSF) pleocytosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently reported immunosuppressive therapy is high dose intravenous (IV) steroids [methylprednisolone, (MP) at least 30/mg/kg/day for at least 3 days] ( 8 , 10–14 ). Additionally, case reports and case series report the use of intravenous immune globulin (IVIG) ( 10 , 15 , 16 ), plasma exchange (PLEX) ( 10 , 16–19 ), and biologics such as tocilizumab (an IL-6 inhibitor) ( 8 , 11 , 19 , 20 ). Supportive care and symptomatic management in an intensive care unit (ICU) is necessary in most cases for depressed mental status, seizure control, blood pressure support, multisystem organ failure management which often requires intubation ( 3 , 8 , 16 , 19 ).…”
Section: Introductionmentioning
confidence: 99%